Genetic Characterization of Small Ovaries, a Gene Required in the Soma for the Development of the Drosophila Ovary and the Female Germline - Wayne, S. (1995)
The small ovary gene (sov) is required for the development of the Drosophila ovary. Six EMS-induced recessive alleles have been identified. Hypomorphic alleles are female sterile and have no effect on male fertility, whereas more severe mutations result in lethality. The female-sterile alleles produce a range of mutant phenotypes that affect the differentiation of both somatic and germline tissues. These mutations generally produce small ovaries that contain few egg cysts and disorganized ovarioles, and in the most extreme case no ovarian tissue is present. The mutant egg cysts that develop have aberrant morphology, including abnormal numbers of nurse cells and patches of necrotic cells. We demonstrate that sov gene expression is not required in the germline for the development of functional egg cysts. This indicates that the sov function is somatic dependent. We present evidence using loss-of-function and constitutive forms of the somatic sex regulatory genes that sov activity is essential for the development of the somatic ovary regardless of the chromosomal sex of the fly. In addition, the genetic mapping of the sov locus is presented, including the characterization of two lethal sov alleles and complementation mapping with existing rearrangements.